Data Analytics on Indonesia Industries Economic Resilience Based on Poverty Rate Growth During Covid-19 Pandemic - Adhi Dharma Wibawa; Lukas Purba Wasesa; Wridhasari Hayuningtyas (JAREE (Journal on Advanced Research in Electrical Engineering), 2022)
Covid-19 pandemic is one of the biggest challenges that each country around the world has to overcome. This pandemic has affected a lot of countries in many sectors including Indonesia. During the year 2020 when Covid-19 cases rise in Indonesia, the poverty rate has also increased by 0.97% meaning almost 270.000 people went poor. Understanding the impact and the resilience especially on the primary industry during the Covid-19 situation is important to decrease the poverty rate as well as create new alternative strategies for the government to overcome. However, the economic resilience of primary industries such as fishing and plantation is still less to explore. In this study, the economic resilience of four major industries in Indonesia when facing the Covid-19 pandemic is presented namely tourism, fishery, plantation, and micro and small business. Bivariate correlation analysis is applied to calculate the statistical correlation between the growth of poverty rate during the Covid-19 pandemic with four major industries in 34 provinces. Based on the result, it can be concluded that plantation industries are the most resilient industries while facing the Covid-19 pandemic, so the provinces with plantation industries as their main industry are less likely to have major growth in poverty rate compared to other provinces with fewer plantation industries. The second most resilient industry is fishing. Meanwhile, the tourism industry is the most vulnerable during the pandemic situation. In this study, the qualitative analysis especially in Riau and Bali provinces is also presented.